Sexual selection and the evolution of sperm morphology in sharks. (19th August 2019) - Rowley, Amy; Locatello, Lisa; Kahrl, Ariel; Rego, Mariana; Boussard, Annika; Garza‐Gisholt, Eduardo; Kempster, Ryan M.; Collin, Shaun P.; Giacomello, Eva; Follesa, Maria C.; Porcu, Cristina; Evans, Jonathan P.; et al.
Abstract: Post‐copulatory sexual selection, and sperm competition in particular, is a powerful selective force shaping the evolution of sperm morphology. Although mounting evidence suggests that post‐copulatory sexual selection influences the evolution of sperm morphology among species, recent evidence also suggests that sperm competition influences variation in sperm morphology at the intraspecific level. However, contradictory empirical results and limited taxonomic scope have led to difficulty in assessing the generality of sperm morphological responses to variation in the strength of sperm competition. Here, we use phylogenetically controlled analyses to explore the effects of sperm competition on sperm morphology and variance in sharks, a basal vertebrate group characterized by wide variation in rates of multiple mating by females, and consequently sperm competition risk. Our analyses reveal that shark species experiencing greater levels of sperm competition produce sperm with longer flagella and that sperm flagellum length is less variable in species under higher sperm competition risk. In contrast, neither the length of the sperm head and midpiece nor variation in sperm head and midpiece length was associated with sperm competition risk. Our findings demonstrate that selection influences both the inter‐ and intraspecific variation in sperm morphology and suggest that the flagellum is an important target of sexual selection in sharks. These findings provide important insight into patterns of selection on the ejaculate in a basal vertebrate lineage. Abstract :